Pengaplikasian Sikap Wara’ dan Zuhud Dalam Kehidupan Nyata - Nasution, Katsron Muhsin (Al-Fikru: Jurnal Ilmiah, 2021)
Many practices that we can do to get closer to Allah Ta’ala. Among others, by taking the path of kindness in order to achieve His blessing. Committing a deed is inseparable from one’s morals, if he has good morals, hopefully his deeds are also good in nature. But that does not mean in achieving good we can do it without rules, we must understand very well, that is sincere intention and the right way (Ahsannul Deeds). If we do a practice with sincere intentions, but the wrong way is not necessarily we can achieve the blessing of Allah and our practice is not the best practice. Vice versa if we do it right, but the intention is not sincere then it is the same as the explanation that has been explained earlier. Similar to our attitude as Muslims, we must have good morals like the Wara’ and Zuhud attitude. Because the attitude of Wara ’and Zuhud are also morals and practices that must be carried out by every Muslim. Now, to find out what is Wara ’and Zuhud we will discuss it in detail in this paper